Electronic voting : first International Joint Conference, E-Vote-ID 2016, Bregenz, Austria, October 18-21, 2016, proceedings /: first International Joint Conference, E-Vote-ID 2016, Bregenz, Austria, October 18-21, 2016, proceedings. (2017) - Unknown
No abstract available